2021
DOI: 10.3390/biom11081128
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones as Inhibitors of SOS RAS-GEF Activity

Abstract: Recent breakthroughs have reignited interest in RAS GEFs as direct therapeutic targets. To search for new inhibitors of SOS GEF activity, a repository of known/approved compounds (NIH-NACTS) and a library of new marine compounds (Biomar Microbial Technologies) were screened by means of in vitro RAS-GEF assays using purified, bacterially expressed SOS and RAS constructs. Interestingly, all inhibitors identified in our screenings (two per library) shared related chemical structures belonging to the anthraquinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Consistent with our observations, and regarding potential new therapeutic approaches to CML, some recent reports have described an increased sensitivity of AML leukemia to mitotoxic drugs or that targeting mitochondrial OXPHOX eradicates therapy-resistant CML stem cells [ 51 , 52 ]. In particular, a recent report indicated that targeting SOS1 overcomes imatinib resistance in CML [ 53 , 54 ], raising interest in clinical testing against CMLs for various recently developed small-molecular antiSOS1 drugs [ 28 , 55 , 56 , 57 , 58 , 59 ], which could prove particularly useful as an alternative when resistances frequently arise after sustained treatment with the classical imatinib or other second-generation TKI inhibitors [ 8 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our observations, and regarding potential new therapeutic approaches to CML, some recent reports have described an increased sensitivity of AML leukemia to mitotoxic drugs or that targeting mitochondrial OXPHOX eradicates therapy-resistant CML stem cells [ 51 , 52 ]. In particular, a recent report indicated that targeting SOS1 overcomes imatinib resistance in CML [ 53 , 54 ], raising interest in clinical testing against CMLs for various recently developed small-molecular antiSOS1 drugs [ 28 , 55 , 56 , 57 , 58 , 59 ], which could prove particularly useful as an alternative when resistances frequently arise after sustained treatment with the classical imatinib or other second-generation TKI inhibitors [ 8 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We managed to bypass the embryonic lethality of SOS1-KO alleles by using a floxed, tamoxifen-inducible SOS1 null mutation that allowed the generation and parallel analysis of the adult, viable mice of four relevant SOS genotypes (WT, SOS1-KO, SOS2-KO, and SOS1/2-DKO). Using this genetic KO system, we recently demonstrated the functional prevalence of SOS1 over SOS2 regarding the control of MEF cellular proliferation and viability, as well as a direct mechanistic link between SOS1 and the control of intracellular mitochondrial redox homeostasis [ 19 , 26 ], and we also characterized the specific functional roles of SOS1 and SOS2 in different biological contexts [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Santos and co-workers identified anthraquinones as SOS1 inhibitors from two libraries of nearly 1000 compounds by using a fluorescence-based nucleotide exchange assay. 98 Four compounds including idarubicin ( 42), doxor- ubicin (43), CL0292 (44), and CL0294 (45) blocked the activation of all canonical RAS isoforms by SOS with micromolar IC 50 values (Figure 14). These anthraquinone compounds were able to reduce the overall RAS activation on the SOS2-KO mouse embryonic fibroblasts (MEFs) but did not suppress the RAS activation in the wild type MEFs.…”
Section: Sos1 Inhibitorsmentioning
confidence: 99%
“…Recently, Santos and co-workers identified anthraquinones as SOS1 inhibitors from two libraries of nearly 1000 compounds by using a fluorescence-based nucleotide exchange assay . Four compounds including idarubicin ( 42 ), doxorubicin ( 43 ), CL0292 ( 44 ), and CL0294 ( 45 ) blocked the activation of all canonical RAS isoforms by SOS with micromolar IC 50 values (Figure ).…”
Section: Small Molecules Targeting Sos1mentioning
confidence: 99%
“…Meanwhile, study by [13] showed that the autoregulatory negative feedback loop involving regulation of p53 by Murine Double Minute 2 (MDM2) could be a novel target therapy in cancer treatment as these two genes regulate each other mutually through an autoregulatory negative feedback loop. Plenty of evidence suggests the competent anticancer effect of anthraquinone against various genes and human cancers, including our target genes: β-catenin [14], MDM2-p53 [15][16][17], and KRAS [18,19]. Given the lack of research elucidating the effect of anthraquinone in CRC, this study aim to discover novel potential inhibitors based on anthraquinones from Morinda citrifolia through the deployment of ligand-based protein docking for β-catenin, MDM2-p53 and KRAS.…”
Section: Introductionmentioning
confidence: 99%